Voluntary Societies and the Process of Middle-class Formation in Early-Victorian Halifax, Nova Scotia - Sutherland, David (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1994)
AbstractThrough the second quarter of the nineteenth century Halifax, Nova Scotia evolved from garrison town to commercial city. That transition, combined with a mass influx of immigrants, spawned unprecedented social dislocation and conflict. Those situated between the extremes of wealth and poverty responded, in part, by flocking into a host of voluntary societies set up to promote social stability as well as material and moral progress. Most influential among all these societies were those which stressed the element of fraternal bonding. They led with respect to forging the disparate "middling" elements of the community into something which, in terms of cohesion and consciousness, could be termed a "middle class".